PROMOTING ENTREPRENEURSHIP AND INNOVATION WITHIN ORGANISATIONS: A LITERATURE REVIEW ON STRATEGIES FOR DEVELOPING AN INNOVATIVE CULTURE, TRANSFORMATIONAL LEADERSHIP, AND ORGANISATIONAL LEARNING DYNAMICS TOWARDS SUSTAINABLE COMPETITIVE ADVANTAGE - Wulandari Wulandari; Hadenan Towpek (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to review the literature on strategies for developing entrepreneurship and innovation within organisations, focusing on three main aspects: innovative culture, transformational leadership, and organisational learning dynamics. Through a systematic literature review approach, this study identifies various best practices that organisations can implement to create a work environment that supports creativity, collaboration, and internal entrepreneurial initiatives. The results of the review show that the synergy between a strong innovative culture, inspirational transformational leadership, and a dynamic organisational learning process is the main foundation for achieving sustainable competitive advantage. The theoretical and practical implications of these findings are expected to assist in the development of innovation management models and organisational strategies that are adaptive to rapid and complex changes in the business environment.